Biochemical characterization of a β-N-acetylhexosaminidase from Catenibacterium mitsuokai suitable for the synthesis of lacto-N-triose II. (March 2021) - Liu, Yihao; Ma, Junwen; Shi, Ran; Li, Ting; Yan, Qiaojuan; Jiang, Zhengqiang; Yang, Shaoqing
Graphical abstract: Highlights: A novel β- N -acetylhexosaminidase gene ( CmHex187 ) was expressed in E. coli . CmHex187 was purified and biochemically characterized. An efficient bioprocess for LNT2 synthesis was developed. The LNT2 conversion ratio of 44.3 % was obtained. LNT2 exhibited higher prebiotic activity compared to fructooligosaccharides (FOS). Abstract: β- N -acetylhexosaminidases have gained much attention for synthesis of functional oligosaccharides, but the relatively low conversion ratio limited their industrial applications. A β- N -acetylhexosaminidase gene ( CmHex187 ) from Catenibacterium mitsuokai was successfully expressed in Escherichia coli . The recombinant enzyme (CmHex187) was purified, biochemically characterized and subjected to the synthesis of human milk oligosaccharides (HMOs). CmHex187 displayed optimal pH and temperature of 5.5 and 45 °C, respectively. The enzyme showed strong transglycosylation activity, as it efficiently catalyzed the synthesis of an important component of HMO lacto- N -triose II (LNT2) using 0.015 M p -nitrophenyl N -acetyl-β-d -glucosaminide and 1.2 M lactose at pH 7.0 and 60 °C for 1.5 h, with a high conversion ratio of 44.3 %. The formed LNT2 promoted the growth of tested Lactobacillus and Bifidobacteria strains. The excellent enzymatic properties and high LNT2 synthesis ability of CmHex187 may make it a good candidate in LNT2 production.